The Influence of Liberal Christian Theology on the Development of Constitutionalism in Late Qing and Early Republican China - LI , Jiale (Journal of Research for Christianity in China (JRCC), 2025)
Academic and intellectual circles have produced numerous specialized works on the contributions of Christianity—particularly Protestantism following the Reformation—to the cause of constitutional government. From the perspective of Christian faith and culture, all political issues can ultimately be traced back to theological questions. This is because differing theological confessions inevitably lead to divergent values and political stances, which in turn shape the distinct political behaviors and practices of individuals and groups. Such differences profoundly influence the choice of a nation's entire political path. Although Christian denominations are numerous (due to complex socio-historical, cultural, and political factors), theologians can be broadly categorized into two main camps based on their degree of adherence to the Bible's comprehensive doctrine and the gospel of salvation: fundamentalist theology and liberal theology. It is widely acknowledged that fundamentalist theology, exemplified by Calvinism, profoundly influenced the establishment of Anglo-American constitutional systems. This paper aims to analyze the impact of liberal Christian theological thought on the trajectory of constitutionalism in late Qing and early Republican China.
Keywords: Christianity, liberal theology, constitutionalism in China during the late Qing and early Republican periods